The reciprocal determinism of online scaffolding in sustaining a community of inquiry in physics - Romiro Gordo Bautista (OmniaScience, 2013)
This study investigated the learning impact of online scaffolding in sustaining a community of inquiry in Physics instruction. The students' a-priori e-learning activities in online discussion were used in leveraging the learning behaviors of the students. Online learning segments were included in the process of developing classroom tasks vis-à-vis with the course intended learning outcomes. This was done in a collegial, constructive and democratic learning towards classroom efficacy through online scaffolding techniques. Two sections of 34 students enrolled in NATSC1D (University Physics 1) were used in this study. A questionnaire was adopted in determining the perceived relative magnitude of advantages of the online discussion. Pearson-r correlation results showed a very-highly positive correlation between the students' a-priori e-learning experiences in online discussion and their success in online scaffolding, and a highly to very-highly positive correlation to their performance in classroom interaction, formative assessment and summative evaluations.